Adherencia a guías de manejo de emergencias obstétricas en muerte materna, Hospital Carlos Monge Medrano 2020 - Pumapillo Garcia, Ana Sarai (2022)
Objective: Determine degree of adherence to the Clinical Practice Guidelines for Attention of Obstetric Emergencies (hypertensive, hemorrhagic and sepsis disorders) in maternal deaths occurred at the Carlos Monge Medrano Hospital (HCMM) of Juliaca in 2020. Method: Quantitative, descriptive, retrospective, observational and cross-sectional study. Medical records of all maternal deaths in HCMM in 2020 were reviewed, using instrument for the evaluation of adherence to Clinical Practice Guidelines (CPG), previously validated, based on an instrument of the Mexican Institute of Social Security, adapting it to CPG recommendations of Ministry of Health of Peru. (Degree of agreement between judges 97.1%). The database was prepared in Excel, processed, and analyzed in SPSS version 27.0. Results: Of the 7 clinical histories of maternal death, it was found in general low and medium adherence to CPG, both with 42.9%; and high adherence only 14.3%. Regarding sociodemographic characteristics, approximately 85% had Comprehensive Health Insurance (SIS), the mean age of the deceased mothers was 35 years, and 85.7% came from Puno, majority were cohabiting and had completed secondary school. The most frequent disorders were hypertensive and hemorrhagic, both with 42.9%.